Official Opening of Zhulian-USM Joint Laboratory on 1 November 2014 - PPTI, Pusat Pengajian Teknologi Industri (PPTI, Pusat Pengajian Teknologi Industri, 2014)
The School of Industrial Technology, Universiti Sains Malaysia (USM) has recently erected a seven-storey building with the primary aim of housing a new Program, the Bioprocess Technology Program. In addition to offices, functional rooms and a pilot plant, this new building will also house several research laboratories. These laboratories will be equipped for teaching and research activities including those for postgraduate studies (PhDs and MScs) under the Bioprocess Technology Program. Zhulian Marketing (M) Sdn. Bhd. has funded the development of several research laboratories, via a contribution of RM 500,000. The laboratories were officiated on 1st November 2014.